Nanobody-Targeted Photodynamic Therapy Selectively Kills Viral GPCR-Expressing Glioblastoma Cells - De Groof, Timo W. M. (Mol Pharm, 2019)
[Image: see text] Photodynamic therapy (PDT) eradicates tumors by the local activation of a photosensitizer with near-infrared light. One of the aspects hampering the clinical use of PDT is the poor selectivity of the photosensitizer. To improve this, we have recently introduced a new approach for targeted PDT by conjugating photosensitizers to nanobodies. Diverse G protein-coupled receptors (GPCRs) show aberrant overexpression in tumors and are therefore interesting targets in cancer therapy. Here we show that GPCR-targeting nanobodies can be used in targeted PDT. We have developed a nanobody binding the extracellular side of the viral GPCR US28, which is detected in tumors like glioblastoma. The nanobody was site-directionally conjugated to the water-soluble photosensitizer IRDye700DX. This nanobody–photosensitizer conjugate selectively killed US28-expressing glioblastoma cells both in 2D and 3D cultures upon illumination with near-infrared light. This is the first example employing a GPCR as target for nanobody-directed PDT. With the emerging role of GPCRs in cancer, this data provides a new angle for exploiting this large family of receptors for targeted therapies.